Les Plantagenêts vus par un abbé du xve siècle : l’article « Anglia » du Granarium de John Wheathampstead - Élisa Mantienne (Bulletin du Centre d’Études Médiévales d’Auxerre)
This paper deals with the image of Plantagenet kings as represented in a 15th century encyclopedia : the Granarium, composed by John Wheathampstead the Benedictine abbot of the monastery of St Albans. More precisely, we will study the short text called « Anglia », which is a narrative of the reigns of the English kings from the mythical origins of England to king Henry V’s death. It is all together an entry of encyclopedia, a short chronicle and a mirror for princes. The paper tries to better understand the aims of John Wheathampstead when he wrote this text. We would argue that this narrative was aimed to be read by members of Henry VI’s court. Some details encourage us to think that it was an appeal to pursue the war in France, in a time when the voices of partisans of peace raised in England.